Een kamer voor jezelf - Woolf, Virginia (Amsterdam : De Bezige Bij, 1979)
Fonds Suzan Daniel (FSD)
Oorspronkelijke titel : a room of one’s own
Vertaling C. E. van der Waals-Nachenius
Nederlands
Monografie